2020
DOI: 10.1097/phm.0000000000001567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow Restriction Training on Muscle Strength and Pain in Patients With Knee Injuries

Abstract: Background Due to the pain caused by knee injuries, low-load resistance training with blood flow restriction (L-BFR) may be a potential adjuvant therapeutic tool in the rehabilitation of knee injuries. This review aimed to analyze the effectiveness of L-BFR training modality in knee rehabilitation. Design A meta-analysis was conducted to determine the potential impact of blood flow restriction on patients with knee injuries. PubMed, EBSCO, and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Except for 4 post-strength assessments [4,19,23,24] statistical significance beyond the comparison (non-BFR low-intensity training) group was achieved in 78% (n = 14) of the included trials (n = 18 strength assessments). The results are in line with other reviews investigating longer-term effects (> 3 weeks) of BFR training on muscle strength in mostly older adults [29], and those with knee injuries [30]. However, as this review was not a metaanalysis and relied on qualitative syntheses, caution is warranted in making firmer conclusions regarding the potential of HF-BFR to induce similar strength gains as longer duration protocols.…”
Section: General Findings Identified In High-frequency Bfr Applicatio...supporting
confidence: 86%
“…Except for 4 post-strength assessments [4,19,23,24] statistical significance beyond the comparison (non-BFR low-intensity training) group was achieved in 78% (n = 14) of the included trials (n = 18 strength assessments). The results are in line with other reviews investigating longer-term effects (> 3 weeks) of BFR training on muscle strength in mostly older adults [29], and those with knee injuries [30]. However, as this review was not a metaanalysis and relied on qualitative syntheses, caution is warranted in making firmer conclusions regarding the potential of HF-BFR to induce similar strength gains as longer duration protocols.…”
Section: General Findings Identified In High-frequency Bfr Applicatio...supporting
confidence: 86%
“…Anorexia and fatigue were often related to reduced energy intake, which lead to malnutrition and muscle strength. There were some researches that have proved the greater muscle strength was associated with less pain [ 37 , 49 , 50 ]. A randomized controlled trial revealed muscle strengthening and balancing exercises were effective in reducing chemotherapy-induced peripheral neuropathic pain and improving QOL among cancer patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address the current limitation, attention should be focused on specific grades of OA to produce more accurate findings. Lastly, further studies should investigate the influence of other potentially moment-modifying factors (e.g., toe-out angle, lateral trunk lean, varus-valgus knee laxity, bracing, insole wedges, and knee malalignment) as well as increased muscle strength 52 on normalizing joint loading to determine other crucial biomechanical factors.…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%